Flexible specialization as locational advantage in the economic crisis? Examples from the German mechanical engineering industry - Martina Fuchs; Hanno Kempermann (European Regional Science Association (ERSA), 2010)
In 2008/2009, the recent economic crisis affected German engine building industries. The incoming orders dropped dramatically. As some regions especially in western and southern Germany are strongly dependent on such industries, the companies as well as the regions, where the companies are located, were endangered. Yet, some companies could implement strategies to overcome the crisis. Such companies were especially such with extended innovation strategies and flexible specialization (Piore/Sabel 1985), producing in niche markets, sometimes in the position as "hidden champions" on the global markets. Besides, the equity ratio of the companies played an important role. In addition to such company-specific assets, there were also political instruments to regulate the labour market which coined the crisis in Germany: especially short-time work and temporary work. Engineering industries, being a knowledge-intensive sector, used such instruments to keep the permanent stuff, as engineers and technicians. Yet, nearly all temporary workers lost their jobs and were the loser of the crisis. In this framework of company-specific and labour-market specific conditions, some engineering building companies developed specific innovation strategies to overcome the crisis. The paper discusses the opportunities and limits for engineering companies to develop strategies to improve the regional employment situation, on the background of company specific conditions (flexible/standardized production; equity ratio) and external conditions (short-time work and temporary work).
Keywords: 330